CAPITAL ADEQUACY MEETS OPERATIONAL EFFICIENCY: A DUAL APPROACH TO ENHANCING PROFITABILITY - Sindik Widati; Angga Deni Pratama; Dian Sulistyorini Wulandari (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to examine the effect of profitability on capital adequacy, with operational efficiency as a moderating variable in the banking sector. The data employed are secondary data from the annual financial reports of commercial banks listed from 2018 to 2023. A quantitative approach using panel data regression was used to test the relationships among variables. The results indicate that profitability has a positive and statistically significant effect on capital adequacy. However, operational efficiency does not significantly moderate this relationship. These findings suggest that while profitability plays a key role in capital planning, the moderating impact of operational efficiency is limited in the context of the sampled banks. This research provides insights for policymakers and bank managers on the strategic role of sustainable profitability in capital management, independent of internal operational enhancements.